Safety and efficacy of Probion Forte® (Bacillus subtilis KCCM 10941P and Bacillus coagulans KCCM 11093P) as a feed additive for chickens for fattening - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Guido Rychen; Gabriele Aquilina; Giovanna Azimonti; Vasileios Bampidis; Maria de Lourdes Bastos; Georges Bories; Andrew Chesson; Pier Sandro Cocconcelli; Gerhard Flachowsky; Jürgen Gropp; Boris Kolar; et al. (EFSA Journal, 2017)
Abstract Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Probion Forte® when used in feed for chickens for fattening. Probion Forte® is a preparation containing viable spores of a strain of Bacillus subtilis and Bacillus coagulans intended for use in feed for chickens for fattening at the minimum dose of 1 × 108 and a maximum of 2 × 108 colony‐forming units (CFU)/kg feedingstuffs. In the view of the FEEDAP Panel, the identity of the bacterial strains is established as B. subtilis and B. coagulans and their susceptibility to relevant antibiotics is demonstrated. However, both bacterial strains belong to species capable of producing toxins. The absence of a toxigenic potential has not been demonstrated and, therefore, these strains do not qualify for a qualified presumption of safety (QPS) approach to safety assessment and separate studies on target animals and consumer safety are required. The data provided did not allow concluding on the safety for chickens for fattening or the consumers. Probion Forte® is not a skin or eye irritant but should be considered a potential respiratory sensitiser. No conclusion can be drawn on the skin sensitisation potential of the additive. In the absence of evidence that the two active agents are not toxigenic, Probion Forte® is considered as a hazard for those handling the additive. Probion Forte® is considered safe for the environment. The FEEDAP Panel is not in the position to conclude on the efficacy of Probion Forte® for chickens for fattening from the data provided.